Clinical value of arterial blood flow signals in endometrial area in outcomes of freeze-thawed embryo transfer - GOU Wenjie (Di-san junyi daxue xuebao, 2019)
Objective To analyze the clinical value of arterial blood flow signals in the endometrial area in the outcomes of freeze-thawed embryo transfer (FET). Methods A total of 175 FET cycles in our special hospital from October 2015 to March 2017 were retrospectively analyzed, and the endometrial areas when endometrial thickness over 7 mm were detected the endometrial arterial blood flow signals with color Doppler ultrasonography. The cases were divided into 3 groups according to the numbers of endometrial arterial blood flow signals < 2, 2~5, and ≥6. Pregnancy outcomes, such as embryo implantation rate, biochemical pregnancy rate, clinical pregnancy rate, ectopic pregnancy rate and early abortion rate were followed up in all the cases. Results The embryo implantation rate and clinical pregnancy rate were statistically lower in those with the number of endometrial arterial blood flow signals < 2 than those with that of 2~5 and ≥6 (P < 0.05), but no such difference were seen between the 2 latter groups (P>0.05). There were no significant differences in biochemical pregnancy rate and early abortion rate among the 3 groups (P>0.05). Logistic regression analysis showed that the number of endometrial arterial blood signals were correlated with clinical pregnancy in those with the number of signals 2~5 and ≥6 (OR=4.33, 95%CI: 1.24~15.19; OR=4.70, 95%CI: 1.21~ 18.28, P < 0.05). Conclusion The fewer arterial blood flow signals in the endometrial area are, the lower embryo implantation rate and clinical pregnancy rate.